Gran casa - GGMPU arquitectos (2001)
Casa ubicada en el Country Jockey Club Córdoba.
Keywords: CORDOBA; ARGENTINA; VIVIENDAS UNIFAMILIARES; GRAMATICA, SARA; GUERRERO, JUAN; MORINI, JORGE; PISANI, JOSE; URTUBEY, EDUARDO; COUNTRY CLUBS